Privilege, Economy and State in Old Regime France : Marine Insurance, War and the Atlantic Empire under Louis XIV. (Boydell & Brewer, Incorporated, 2023)
This book reveals a great deal about the attempts, and failures, of the French absolutist monarchy to stimulate commerce, colonial enterprise and economic growth, and how these attempts and failures contrasted with the successes of Amsterdam and London.